Penerapan Pronasi dan Semi Fowler terhadap Peningkatan Saturasi Oksigen pada Pasien COVID-19 - Sri Mulati Nendah Agreta; Nyimas Heny Purwati; Fitrian Rayasari; Rohman Azzam (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effectiveness of prone and semi-fowler positions on oxygen saturation in COVID-19 pneumonia patients at the Jakarta Islamic Hospital Cempaka Putih. The quantitative method uses quasi-experimental data analysis techniques with a two-group preintervention-postintervention design. The results of the bivariate analysis with the T-test showed the value of Sig. P â‰¥ 0.05 found that the average before and after holding the prone position was 97%, and the pre-and post-intervention standards in the semi-Fowler class were 95% oxygen saturation. The value of this difference in oxygen saturation is influenced by age, sex, BMI, and HB, so the results affect the difference in pronation position, which is more effective than semi-fowler with the criterion of increasing oxygen saturation above the standard oximeter value, where pronation intervention in COVID-19 patients is more effective from semi fowler with the measure of an increase in oxygen saturation above 95%. In conclusion, there are different changes in oxygen saturation before and after the prone, and semi-fowler positions are carried out in COVID-19 pneumonia patients at the Jakarta Islamic Hospital Cempaka Putih. Keywords: COVID-19, Pronation, Oxygen Saturation, Semi Fowler